Yao-Shan of traditional Chinese medicine: an old story for metabolic health - Yang, Shuangling; Yang, Hongzhi; Zhang, Yaxing (Frontiers in Pharmacology, 2023)
Type 2 diabetes mellitus, nonalcoholic fatty liver diseases (NAFLD), cardio-cerebrovascular diseases (CCVDs), hyperuricemia and gout, metabolic related sexual dysfunction, are set of metabolic diseases that affect modern human health. Scientists have made great efforts using cell models in vitro or animal models in the past, however, the findings from cells or animals are difficult to translate into clinical due to the differences between in vitro and in vivo, and the differences between human and animals in their anatomy, physiology, genetics, and the microbiome-host interaction, among other factors. The Chinese people have extensively used the medicated diet of the traditional Chinese medicine (TCM) (also referred as “dietotherapy”, Yao-Shan of TCM) to maintain or improve cardiometabolic health for more than 2200 years. These ancient classic diets of TCM are the essential summaries of the long-term life practice and clinical practice. During the past five years, our group has made every effort to collect and sort out the classical Yao-Shan of TCM related to the prevention and treatment of modern metabolic diseases, such as diabetes, NAFLD, CCVDs, hyperuricemia and gout, and sexual dysfunction, from these ancient TCM literatures since Spring & Autumn and Warring States Period. Here, we summarized and discussed the classical Yao-Shan of TCM for metabolic diseases according to the time recorded in the literature. We have verified modern names of the raw materials in Yao-Shan of TCM, and attached their Latin names in text and marked their Chinese names in the appendix. We also enhanced current progresses of some Yao-Shan of TCM by the modern medicine strategies. Yao-Shan of TCM have exact therapeutic effects, however, the exact composition (in terms of ratios), the preparation process, and dosage of these Yao-Shan are not standardized, and their main active ingredients are vague. Uncovering the mystery of Yao-Shan of TCM by modern biological and chemical strategies will help us open a door, which is ancient but now looks new, to modulate metabolic homeostasis and diseases.